REKONSTRUKSI KOTA KOLONIAL SALATIGA DAN KONTRIBUSI TEKNOLOGI GEOGRAPHICAL INFORMATION SYSTEM - Muh Khoirul Anwar (SASDAYA: Gadjah Mada Journal of Humanities, 2019)
Salatiga City was located on the hillside of Merbabu Mountain and on highland has fresh air and cool climate. Salatiga City also located on the strategist area, reachable from Semarang, Solo, Ambarawa, and Magelang. Salatiga is very interesting for Europeans that live there in the Colonial Era. The implication for Modern Salatiga is to many historical buildings with classical European style in Salatiga. There is a well-preserved building, but also the same building was not preserved and destroyed. The historical building is a cultural heritage and national treasure that can be used for many good things, such as science or economics. To raise the awareness of the folk about historical buildings, we need to make publications and educate the folk about how important the historical building was. To get the publication material and education material was held historical research with a technical approach in a form of using Geographical Information System as research tools. As expected from this research can raise the awareness of the folks about how important the historical building.